SOME FEATURES OF TEACHING OF STOMATOLOGY TO FOREIGN STUDENTS IN DONETSK NATIONAL MEDICAL UNIVERSITY - А.V. Mahniova (Український стоматологічний альманах)
Authors share experience of teaching of stomatology to the foreign students in the Donetsk National Medical University. The department of stomatology provides teaching to the foreign students by forces of highly skilled professors and associate professors. The department of stomatology published the methodical guidelines for Russian talking and English talking foreign students. The teaching aid was published, which uses the celebrated popularity at foreign students. A lecture course remains the leading link of educational process in the university. A lecture install bases of scientific knowledge, makes a theoretical base for the studied discipline, acquaints students with methodology of researches, serves as a point and work of students assignment specifies on all of other types of educational process.